Design and Construction of a Web-Based Inventory Information System Using the First In First Out (FIFO) Method at the Samanda Store - Titi Wideratna; Yuri Nurul Hidayah; Ade Supriatna (LPPM STMIK Mardira Indonesia, 2026)
The fashion sector confronts progressively intricate issues in the contemporary digital world. Swiftly evolving fashion microtrends require enterprises to adopt stringent inventory and supply chain management practices to maintain competitiveness. Toko Samanda, a fashion retail establishment, faces immediate consequences of these micro-trends, including ineffective inventory management, intuition-driven restocking, and manual recording inaccuracies that lead to overstocking. As a result, increased warehouse inventory risks diminishing market appeal, thereby decreasing selling value. Progress in information technology underscores the need for effective inventory management, especially for small enterprises such as Toko Samanda, which hitherto relied on manual record-keeping. This research aims to design and develop a web-based inventory information system using the First In First Out (FIFO) method to optimize stock management. The researcher utilized the Object-Oriented Analysis and Design (OOAD) methodology to construct the system. The system's functionality includes managing data for employees, categories, items, suppliers, and customers, processing procurement and sales transactions, and generating inventory reports. System testing through Black-box Testing and User Acceptance Testing (UAT), using Toko Samanda's personnel, resulted in a satisfaction rate of 95.19% (Grade A). The application of the FIFO approach efficiently governs the movement of items, improves accuracy and processing velocity, and facilitates more informed management decision-making.